2015
DOI: 10.1016/j.nuclphysb.2015.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Rational quantum integrable systems ofDNtype with polarized spin reversal operators

Abstract: We study the spin Calogero model of D N type with polarized spin reversal operators, as well as its associated spin chain of Haldane-Shastry type, both in the antiferromagnetic and ferromagnetic cases. We compute the spectrum and the partition function of the former model in closed form, from which we derive an exact formula for the chain's partition function in terms of products of partition functions of Polychronakos-Frahm spin chains of type A. Using a recursion relation for the latter partition functions t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
(157 reference statements)
0
3
0
Order By: Relevance
“…Finally it should be noted that, apart from the context of the BC N type of spin Calogero model and PF spin chain, the BC N type of Weyl algebra plays a very important role in context of the BC N type of spin Sutherland model, related HS spin chain and also for the cases of supersymmetric generalizations of these models [37,56]. Therefore, one can use the PSRO (2.24) to construct novel exactly solvable variants of the BC N type of spin Sutherland model and HS spin chain [57]. Furthermore, it is also possible to construct supersymmetric generalization of the PSRO (2.24) and apply such operator to find out exactly solvable variants of the supersymmetric spin Calogero model and PF spin chain associated with the BC N root system [58].…”
Section: Discussionmentioning
confidence: 99%
“…Finally it should be noted that, apart from the context of the BC N type of spin Calogero model and PF spin chain, the BC N type of Weyl algebra plays a very important role in context of the BC N type of spin Sutherland model, related HS spin chain and also for the cases of supersymmetric generalizations of these models [37,56]. Therefore, one can use the PSRO (2.24) to construct novel exactly solvable variants of the BC N type of spin Sutherland model and HS spin chain [57]. Furthermore, it is also possible to construct supersymmetric generalization of the PSRO (2.24) and apply such operator to find out exactly solvable variants of the supersymmetric spin Calogero model and PF spin chain associated with the BC N root system [58].…”
Section: Discussionmentioning
confidence: 99%
“…For the special cases like m 1 = m 2 or m 1 = m 2 ± 1, P (m 1 ,m 2 ) i reduces to the spin reversal operator P i (up to a sign factor) through a similarity transformation. Choosing the reflection operators as such PSRO, new exactly solvable spin Calogero models of BC N and D N type have been constructed and the partition functions of the related PF chains have also been computed by using the freezing trick via the direct approach [49,50]. Furthermore, exactly solvable spin Calogero models of BC N type have been constructed by taking reflection operators as supersymmetric analogues of PSRO (SAPSRO) [51].…”
Section: (M)mentioning
confidence: 99%
“…It can be shown that, in some particular cases like m 1 " m 2 or m 1 " m 2 ˘1, P pm 1 ,m 2 q i reduces to the spin reversal operator P i through a similarity transformation. Choosing the reflection operators as such PSRO, new variants of BC N and D N type of PF spin chains have been obtained and the partition functions of these spin chains have also been calculated by using the freezing trick [47,48]. Finally, by choosing the reflection operators as supersymmetric analogues of PSRO (SAPSRO), an even larger class of BC N type of PF spin chains have been obtained [49].…”
Section: Introductionmentioning
confidence: 99%